Therapies and outcomes of congenital hyperinsulinism‐induced hypoglycaemia. Issue 1 (8th October 2018) - Banerjee, I.; Salomon‐Estebanez, M.; Shah, P.; Nicholson, J.; Cosgrove, K. E.; Dunne, M. J.
Abstract: Congenital hyperinsulinism is a rare disease, but is the most frequent cause of persistent and severe hypoglycaemia in early childhood. Hypoglycaemia caused by excessive and dysregulated insulin secretion (hyperinsulinism) from disordered pancreatic β cells can often lead to irreversible brain damage with lifelong neurodisability. Although congenital hyperinsulinism has a genetic cause in a significant proportion (40%) of children, often being the result of mutations in the genes encoding the KATP channel ( ABCC8 and KCNJ11 ), not all children have severe and persistent forms of the disease. In approximately half of those without a genetic mutation, hyperinsulinism may resolve, although timescales are unpredictable. From a histopathology perspective, congenital hyperinsulinism is broadly grouped into diffuse and focal forms, with surgical lesionectomy being the preferred choice of treatment in the latter. In contrast, in diffuse congenital hyperinsulinism, medical treatment is the best option if conservative management is safe and effective. In such cases, children receiving treatment with drugs, such as diazoxide and octreotide, should be monitored for side effects and for signs of reduction in disease severity. If hypoglycaemia is not safely managed by medical therapy, subtotal pancreatectomy may be required; however, persistent hypoglycaemia may continue after surgery and diabetes is an inevitable consequence in later life. It is important to recognize the negative cognitive impact of early‐life hypoglycaemia which affects half of all children with congenital hyperinsulinism. Treatment options should be individualized to the child/young person with congenital hyperinsulinism, with full discussion regarding efficacy, side effects, outcomes and later life impact. What's new?: Congenital hyperinsulinism is a heterogeneous disorder of hypoglycaemia with high morbidity and few therapeutic options. Investigation and treatment principles have been described in several reviews but there has been little emphasis on medium‐ to long‐term outcomes. In the present review, we describe outcomes of congenital hyperinsulinism to provide a long‐range view of the clinical impact of current therapeutic strategies.